2019
DOI: 10.1186/s12909-019-1603-1
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity and mental health of rural-oriented tuition-waived medical students in Anhui Province, China

Abstract: Background The shortage of primary care physicians in rural China is an enduring problem with serious implications for access to care. In response to the shortage in health workforce in rural areas, China government has launched the rural-oriented tuition-waived medical education (RTME) programme since 2010, aiming to train more general practitioners to address the rural health workforce requirements in middle and west areas. This study aims to investigate the prevalence of mental illness and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Qualities of the studies are shown in online Appendix- Table 1. A total of 8 studies [15][16][17][18][19][20][21][22] were assessed at a high risk of bias (modified Newcastle-Ottawa scale < 3 points).…”
Section: Resultsmentioning
confidence: 99%
“…Qualities of the studies are shown in online Appendix- Table 1. A total of 8 studies [15][16][17][18][19][20][21][22] were assessed at a high risk of bias (modified Newcastle-Ottawa scale < 3 points).…”
Section: Resultsmentioning
confidence: 99%
“…China has begun to implement a reform of the medical insurance payment method, and the “pay by individual” method has begun to take effect. This payment method can transform the increased investment in health into an improvement in the income and welfare of medical staff ( 25 ). At the same time, it not only pays attention to the salary of workers, but also pays attention to the fairness and reasonableness of the distribution process ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, [ 30 , 31 ] we found that interest in medicine motivated the students to choose medicine. Motivational theories suggest that students who have higher interest in learning medicine may have higher academic achievement and a higher level of professional identity [ 30 , 32 ]. Career theories argue that career satisfaction and continuance are determined by one’s personal vocational interests and values [ 33 ].…”
Section: Discussionmentioning
confidence: 99%